Epidemiological and clinical profile of pediatric hepatitis B virus infections in Wuhan: a retrospective cohort study - Jun Wang; Yong-guo Huang; Ye Zeng; Qin-zhen Cai; Mo Wu; Xin Shen; Wen-bin Tuo; Si Xie; Xiang Ma; Yun Xiang; Chun-hui Yuan; Cong Yao (BMC, 2023)
Abstract Background Hepatitis B virus (HBV) remains a substantial public health safety concern drawing considerable attention in China and globally. The detection of HBV serological markers can enable the assessment of HBV infection and replication status in vivo and evaluate the body's protection against HBV. Therefore, this study aims to identify the epidemiological and clinical characteristics of HBV infection in children to prevent and control HBV infection in Wuhan areas. Methods We conducted an extensive retrospective cohort analysis of 115,029 individuals aged 0-18 years who underwent HBV serological markers detection for HBV infection in hospital between 2018 and 2021 using Electrochemiluminescence immunoassay. We generated descriptive statistics and analysed HBV infection's epidemiological and clinical characteristics between different sex and age groups. Results The overall positive detection rates of HBsAg, HBsAb, HBeAg, HBeAb, and HBcAb in all participants were 0.13%, 79.09%, 0.17%, 2.81%, and 5.82%, respectively. The positive rate of HBeAb and HBcAb in males was significantly lower than that in females (2.64% vs. 3.13%, 5.56% vs. 6.29%) (P < 0.05). Twenty-two distinct HBV serological expression patterns were revealed. Among them, 8 common expression patterns accounted for 99.63%, while the remaining 14 uncommon expression patterns were primarily observed in neonatal patients with HBV infection. There are no significant differences in serological patterns based on sex (P < 0.05). The overall HBV infection detection rate was 5.82% [range 5.68-5.95] and showed a declining yearly trend. The rate in females was higher than that in males 6.29% [6.05, 6.35] vs. 5.56% [5.39, 5.59]. The overall HBV diagnostic rate over 4 years was 0.20% [0.17, 0.22], and the rate declined yearly. The prevalence of acute infection was higher than that of other infection types before 2019, but the incidence of unclassified infection showed a significant upward trend after 2019. Conclusions While the overall HBV infection detection rate in children has decreased year by year, the infection rate remains high in children under one year and between 4 and 18 years. This continued prevalence warrants heightened attention and vigilance.